Middle School Students’ Ideas about Energy and Its Flow through Organisms - Shome, Saurav; Natarajan, Chitra (JOURNAL OF INDIAN EDUCATION, 2012)
The conceptual pre-requisites for teaching about the environment are embedded in several existing school subjects. However, the teaching of subjects like Science and Social Studies does not address all the linkages needed for environmental education. Topics related to current environmental concerns that are inadequately addressed in classrooms include energy, its flow through organisms, especially in relation to human life. We developed a short course on energy and environment, in which students of Class VIII engaged in a large variety of activities designed to explore their understanding of energy and its flow through life forms, with special emphasis on the link between humans, energy and the environment. This paper reports some of our insights gained through a variety of interactions with students and their implications for teaching.